DESA ADAT LEGIAN DITINJAU DARI POLA DESA TRADISIONAL BALI - Keddy Setiada, Nengah (Jurnal Natah; Vol. 1, No. 2 Juni 2003, 2012)
Bali in essence has an intense arrangement in a various life aspect, including in a settlement matter. Bali is well-known due to it’s unique, not only intern of its building but also on its village pattern. Most villages in Bali mainly have an obvious pattern. Yet, some of them are in fact facing a disparity pattern. The obvious pattern, which can be seen physically, is the village borders as a natural element, and also has kahyangan tiga/kahyangan desa (three abode of the Hindu Gods) in each villages unit. Due to the development of all life aspects lead to the physically development of that village. It is strangely probable that the village pattern is previously obvious, turns out to be obscure since the enlargement of new buildings. To prevent this matter, it will require observing precisely that village particularly on its pattern. Desa Adat Legian Kuta, which rapidly develops, has formerly the obvious pattern as Balinese traditional pattern. This village is classified as a linear pattern by a line basis as the main road that is stretching out on the North-South is in a center of the village. It has the kahyangan tiga/kahyangan desa, the house units are located at edge of the main road and the back is set a dry field (tegalan/teba). It clearly point up that the village border of Desa Adat Legian Kuta is the dry field (tegalan), river and sea.
Keywords: custom/tradition village – village pattern and settlement.